A Quantum-Inspired Model for Bit-Serial SIMD-Parallel Computation - Dietz, Henry; Shafran, Aury; Murphy, Gregory Austin (Languages and Compilers for Parallel Computing, 2022)
Bit-serial SIMD-parallel execution was once commonly used in supercomputers, but fell out of favor as it became practical to implement word-level operations directly in MIMD hardware. Word-level primitive operations simplify programming and significantly speed-up sequential code. However, aggressive gate-level compiler optimization can dramatically reduce power consumed in massively-parallel bit-serial execution without a performance penalty. The model described here, Parallel Bit Pattern Computing, not only leverages gate-level just-in-time optimization of bit-serial code, but also uses a quantum-inspired type of symbolic execution based on regular expressions to obtain a potentially exponential reduction in computational complexity while using entirely conventional computer hardware.